Translating cultures an introduction for translators, interpreters and mediators - Katan, David; Taibi, Mustapha (Routledge, 2021)
"This bestselling coursebook introduces current understanding about culture and provides a model for teaching culture to translators, interpreters and other mediators. The approach is interdisciplinary, with theory from translation studies and beyond, while authentic texts and translations illustrate intercultural issues and strategies adopted to overcome them. This new edition has been thoroughly revised to update scholarship and examples and now includes new languages such as Arabic, Chinese, German, Japanese, Russian, and Spanish, and examples from interpreting settings. The third edition revisits the chapters based on recent developments in scholarship in intercultural communication, cultural mediation, translation and interpreting. It aims to achieve a more balanced representation of written and spoken communication by giving more attention to interpreting than the previous editions, especially in interactional settings. Enriched with discussion of key recent scholarly contributions, each practical example has been revisited and/or updated. Complemented with online resources, which may be used by both teachers and students, this is the ideal resource for all students of translation and interpreting, as well as for any reader interested in communication across cultural divides. Additional resources are available on the Routledge Translation Studies Portal: http://routledgetranslationstudiesportal.com"--